2021
DOI: 10.1111/aogs.14282
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes in women living with HIV‐1 and receiving antiretroviral therapy—a systematic review and meta‐analysis

Abstract: Introduction Antiretroviral therapy‐naïve pregnant women living with HIV are at an increased risk for adverse pregnancy outcomes. It remains controversial whether this risk persists with antiretroviral therapy. We conducted a systematic review and meta‐analysis to evaluate whether pregnant women living with HIV and receiving antiretroviral therapy antenatally, are at an increased risk of adverse outcomes compared with HIV‐negative controls. Material and methods We searched MEDLINE, Embase, International Pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 65 publications
(144 reference statements)
1
13
0
1
Order By: Relevance
“… 4 The risk of adverse birth outcomes is higher as compared to HIV-negative women even for those on antiretroviral therapy (ART). 5 In 2020, there were approximately 1·3 million live births to pregnant women living with human immunodeficiency virus (PWLHIV). 6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 The risk of adverse birth outcomes is higher as compared to HIV-negative women even for those on antiretroviral therapy (ART). 5 In 2020, there were approximately 1·3 million live births to pregnant women living with human immunodeficiency virus (PWLHIV). 6…”
Section: Introductionmentioning
confidence: 99%
“…4 The risk of adverse birth outcomes is higher as compared to HIV-negative women even for those on antiretroviral therapy (ART). 5 In 2020, there were approximately 1¢3 million live births to pregnant women living with human immunodeficiency virus (PWLHIV). 6 The increased metabolic needs of pregnancy are accompanied by morphological changes to the gastrointestinal tract such as villus hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, maternal infections, such as HIV, malaria, syphilis and tuberculosis, have been reported to be associated with adverse perinatal outcomes. [48][49][50][51] However, the influence of these infections may be small in the present study because the prevalence of these maternal infections was very low in Japan.…”
Section: Discussionmentioning
confidence: 66%
“…Although a systematic review has shown that people living with HIV on ART ( n = 12 636) have higher adverse birth outcomes, including preterm birth, low birthweight, and being small for gestational age, compared with women without HIV ( n = 7 812 115) [50], limited data exist specifically assessing the risk of spontaneous abortions among pregnant women on ART compared with women without HIV.…”
Section: Discussionmentioning
confidence: 99%